BS EN 3434. Aerospace series. Nuts, hexagon, slotted / castellated, self-locking, in steel, cadmium plated, MoS2 lubricated. Classification: 900 MPa (at ambient temperature) / 235°C. (3rd December 2020) - British Standards Institution,
No abstract available